A Proposed Concept of Communication Network For Emergency Phases In Banda Aceh - Zahrul Maizi; Nani Eliza; Zuhar Musliyana (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Communication problems during emergency situations caused by diverse natural phenomenon, especially earthquake, often occurred in Banda Aceh. This is due to an increase in user traffic on the communication network that made most of the providers overwhelmed. Therefore, the existence of a sophisticated network infrastructure for an effective communication in time of emergency phase must be provided. Considering the needs for better communication that can lead to efficient responses in disaster emergency, we try to present a concept of Wireless Mesh Network (WMN) as one of the most effective communication network solutions for today that can perform well in crisis phases. This concept is expected to help the local government, related parties, and communities in doing various communication needs in time of crisis phase. The idea of this WMN is also expected to be taken into consideration for all providers in building their network infrastructure in the future.Keywords: emergency phase, communication network, WMN.